Ultrasonographic and progesterone changes during Days 21 to 63 of pregnancy in queens - García Mitacek, María Carla (2015)
Ultrasonography has been used to diagnose and monitor pregnancy. However, in the queen, most of ultrasonographic and endocrinological studies have been performed using small number of observations during limited periods of pregnancy. The aim of this study was to derive equations to predict the gestation age and parturition time using ultrasonographic embryo fetus measurements and serum progesterone (P4) concentration measurements. Mixed-breed queens (n = 16), aged between 24 and 36 months and weighing between 2 and 4 kg, were daily monitored by ultrasonography since 21 days after the first mating to parturition. Gestational sac (GS) was measured from longitudinal (length [LEN], anterior-posterior [ATP]) and transverse images (width [WID]), GS volume was calculated by the prolate ellipse formula, and GS diameter was calculated by orthogonal measurements. Fetal measurements included crown-rump length (CRL), head diameter (HD), and body diameter (BD). Gestational sac, fetal measurements, and serum P4 concentration were recorded and analyzed by ANOVA. Correlation and linear regression analyses were performed and equations were derived to estimate predicted values and 95% confidence interval for GS parameters and P4 concentrations from 21 to 63 days after the first mating and to estimate predicted values and 95% confidence interval for fetal parameters from Day 35 to 63 of gestation. The average concentrations of serum P4 concentration from Day 22 to 47 of gestation remained between 32.27 ± 4.25 and 16.25 ± 2.45 ng/mL. After that, a gradual decline occurs reaching a concentration of 2.99 ± 1.29 ng/mL 1 day before parturition. A positive and significant correlation between the ultrasonographic measurements (LEN, ATP, WID, GS volume and diameter, uterine wall thickness, CRL, HD, and BD) with number of days after the first mating was observed (P < 0.001). We observed a positive and significant correlation between GS measurements (LEN, ATP, and WID) and between fetal measurements (CRL, HD, and BD) and a negative and significant correlation between serum P4 concentration with GS (LEN, ATP, and WID), uterine wall thickness, and fetal (CRL, HD, and BD) measurements. In addition, there was a positive and significant correlation between serum P4 concentrations with days after the first mating to parturition. In conclusion, the equations derived from this study will be useful for pregnancy monitoring and for estimating pregnancy age in queens from Day 21 until parturition for animals with similar weight and age.